Controlled release of hydrogen by implantation of magnesium induces P53-mediated tumor cells apoptosis - Rui Zan; Hao Wang; Weijie Cai; Jiahua Ni; Bérengère J.C. Luthringer-Feyerabend; Wenhui Wang; Hongzhou Peng; Weiping Ji; Jun Yan; Jiazeng Xia; Yang Song; Xiaonong Zhang (Bioactive Materials, 2022)
Hydrogen has been used to suppress tumor growth with considerable efficacy. Inhalation of hydrogen gas and oral ingestion of hydrogen-rich saline are two common systemic routes of hydrogen administration. We have developed a topical delivery method of hydrogen at targeted sites through the degradation of magnesium-based biomaterials. However, the underlying mechanism of hydrogen's role in cancer treatment remains ambiguous. Here, we investigate the mechanism of tumor cell apoptosis triggered by the hydrogen released from magnesium-based biomaterials. We find that the localized release of hydrogen increases the expression level of P53 tumor suppressor proteins, as demonstrated by the in vitro RNA sequencing and protein expression analysis. Then, the P53 proteins disrupt the membrane potential of mitochondria, activate autophagy, suppress the reactive oxygen species in cancer cells, and finally result in tumor suppression. The anti-tumor efficacy of magnesium-based biomaterials is further validated in vivo by inserting magnesium wire into the subcutaneous tumor in a mouse. We also discovered that the minimal hydrogen concentration from magnesium wires to trigger substantial tumor apoptosis is 91.2 μL/mm3 per day, which is much lower than that required for hydrogen inhalation. Taken together, these findings reveal the release of H2 from magnesium-based biomaterial exerts its anti-tumoral activity by activating the P53-mediated lysosome-mitochondria apoptosis signaling pathway, which strengthens the therapeutic potential of this biomaterial as localized anti-tumor treatment.